Multiple Domains of Tetanus Toxin Direct Entry into Primary Neurons. (11th August 2014) - Blum, Faith C.; Tepp, William H.; Johnson, Eric A.; Barbieri, Joseph T.
<x xml:space="preserve">Abstract</x> Tetanus toxin elicits spastic paralysis by cleaving VAMP‐2 to inhibit neurotransmitter release in inhibitory neurons of the central nervous system. As the retrograde transport of tetanus neurotoxin (TeNT) from endosomes has been described, the initial steps that define how TeNT initiates trafficking to the retrograde system are undefined. This study examines TeNT entry into primary cultured cortical neurons by total internal reflection fluorescence (TIRF) microscopy. The initial association of TeNT with the plasma membrane was dependent upon ganglioside binding, but segregated from synaptophysin1 (Syp1), a synaptic vesicle (SV) protein. TeNT entry was unaffected by membrane depolarization and independent of SV cycling, whereas entry of the receptor‐binding domain of TeNT (HCR/T) was stimulated by membrane depolarization and inhibited by blocking SV cycling. Measurement of the incidence of colocalization showed that TeNT segregated from Syp1, whereas HCR/T colocalized with Syp1. These studies show that while the HCR defines the initial association of TeNT with the cell membrane, regions outside the HCR define how TeNT enters neurons independent of SV cycling. This provides a basis for the unique entry of botulinum toxin and tetanus toxin into neurons. <inline-graphic xlink:href="ark:/27927/pgh1c9m0xrq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />